Strategies to examine new compounds for intraperitoneal use in ovarian cancer. (1st February 2008) - Markman, M.
Abstract : The results of three large well-designed randomized trials demonstrating the favorable impact of primary cisplatin-based chemotherapy on survival in small-volume residual advanced ovarian cancer has stimulated considerable interest in exploration of this route of drug delivery for other antineoplastic agents. A number of relevant properties of both the drugs and the peritoneal cavity need to be considered in preclinical evaluation such that future clinical development will focus on strategies that have a realistic potential for being safe and effective when they enter the clinical arena